Serial Measurements of Cystatin C Are More Accurate Than Creatinine-Based Methods in Detecting Declining Renal Function in Type 1 Diabetes - Erosha Premaratne; Richard J. MacIsaac; Sue Finch; Sianna Panagiotopoulos; Elif I. Ekinci; George Jerums (2008)
Cystatin C-and creatinine-based methods were compared with (99m)-technetium-diethylene-triamine-penta-acetic acid ((99m)Tc-DTPA) plasma clearance (isotopic glomerular filtration rate [iGFR]) for detecting declining renal function.Glomerular filtration rate (GFR) was monitored over a mean of 10.1 years in 85 subjects with type 1 diabetes (with an average of 5.6 measurements per individual). Baseline mean +/- SD iGFR of the cohort was 106.1 +/- 2.6 ml/min per 1.73 m(2). The rates of decline in GFR (DeltaGFR) were derived using linear regression.In 19 of 85 subjects with declining renal function (i.e., DeltaiGFR >3.3 ml/min per 1.73 m(2) per year), DeltaGFR (ml/min per 1.73 m(2) per year) was 6.5 by iGFR, 4.2 by 10(4)/creatinine, 3.6 by Cockcroft-Gault formula, 3.4 by the Modification of Diet in Renal Disease (MDRD)-6 equation, and 3.5 by the MDRD-4 variable equation (P < 0.01 vs. iGFR). In comparison, DeltaGFR was 6.1 using the formula Cys-GFR = (86.7/cystatin C concentration) - 4.2 (not significant).Cystatin C was more accurate in detecting decline in renal function than creatinine-based methods in this population of subjects with type 1 diabetes and a normal mean baseline GFR.